3D finite element analysis of a two-surface wear model in fretting tests - Stéphanie Basseville; Djamel Missoum-Benziane; Georges Cailletaud (Friction)
Abstract This article aims at developing a computationally efficient framework to simulate the erosion of two contact surfaces in three-dimensional (3D), depending on the body resistance. The framework involves finite element (FE) resolution of a fretting problem, wear computation via a non-local criterion including a wear distribution parameter (WDP), as well as updating of the geometry and automatic remeshing. Its originality is based on the capability to capture the damage on each surface and obtain local and global results for a quantitative and qualitative analysis. Numerical simulations are carried out for two 3D contact specimens with different values of WDP. The results highlight the importance of correctly modelling wear: One-surface wear model is sufficient from a global point of view (wear volume), or whenever the wear resistance for a body is much higher than that of another one, whereas a 3D two-surface wear model is essential to capturing local effects (contact pressure, wear footprint, etc.) related to the difference in wear resistance of the bodies.